2015
DOI: 10.3389/fimmu.2015.00428
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of microRNAs in Thymic Epithelial Cells from Trypanosoma cruzi Acutely Infected Mice: Putative Role in Thymic Atrophy

Abstract: A common feature seen in acute infections is a severe atrophy of the thymus. This occurs in the murine model of acute Chagas disease. Moreover, in thymuses from Trypanosoma cruzi acutely infected mice, thymocytes exhibit an increase in the density of fibronectin and laminin integrin-type receptors, with an increase in migratory response ex vivo. Thymic epithelial cells (TEC) play a major role in the intrathymic T cell differentiation. To date, the consequences of molecular changes promoted by parasite infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…Under these conditions, 29 of 85 miRNAs were found to be up-regulated in the TEC of the infected experimental mice compared to the normal mice. Additionally, seven miRNAs (miR-144, miR-291b-3p, miR-208b, miR-295, miR-488, miR-302a, and miR-654-3p) were found to target the genes that can impact the transforming growth factor (TGF)-β signaling pathway, which supported their role in thymic atrophy (Linhares-Lacerda et al 2015). Similar results were obtained in another study of a T. cruziinfected experimental mouse model in which severe ATI was found to be a primary event due to reduction in number of DP cells on day 10 post infection.…”
Section: Parasitic Infections and Atimentioning
confidence: 84%
See 1 more Smart Citation
“…Under these conditions, 29 of 85 miRNAs were found to be up-regulated in the TEC of the infected experimental mice compared to the normal mice. Additionally, seven miRNAs (miR-144, miR-291b-3p, miR-208b, miR-295, miR-488, miR-302a, and miR-654-3p) were found to target the genes that can impact the transforming growth factor (TGF)-β signaling pathway, which supported their role in thymic atrophy (Linhares-Lacerda et al 2015). Similar results were obtained in another study of a T. cruziinfected experimental mouse model in which severe ATI was found to be a primary event due to reduction in number of DP cells on day 10 post infection.…”
Section: Parasitic Infections and Atimentioning
confidence: 84%
“…Moreover, seven modulated miRNAs (miR-144, miR-291b-3p, miR-208b, miR-295, miR-488, miR-302a, and miR-654-3p) that impact the TGF-β signaling pathway were detected, which suggested their considerable role in ATI. Furthermore, putative roles for 29 differentially regulated microRNAs have been demonstrated in B-cell lymphoma 2 (Bcl2)-associated apoptosis, AIRE down-regulation and extracellular matrix deposition (Linhares-Lacerda et al 2015). During Leishmania-and Schistosome-associated inflammation, miR-182 and miR-10a have been found to be main regulators of the CD4 + Foxp3 + Tregs, and the IL-12/ IFN-γ axis regulates miR-10a as well as its putative transcription factor, Creb.…”
Section: Role Of Microrna and Tgf-β Signaling Pathway In Parasitic Inmentioning
confidence: 99%
“…In the last 2 years, several authors (Garcia‐Silva et al, , ; Fernandez‐Calero et al, ; Linhares‐Lacerda et al . , ) have shown that MVs released by T. cruzi could transfer small RNA, particularly tRNA halves, suggesting that these vesicles could modulate the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bayer-Santos et al (2013), found two types of EVs secreted by the parasites. Later, Garcia-Silva et al (2014), Linhares-Lacerda et al (2015), andFernandez-Calero et al (2015) showed the involvement of miRNA in MV transfer to host cells, indicating this mechanism as a novel modulating effect against neighbouring cells.…”
Section: Trofozoites From Giardia Intestinalis Respond To Environmentmentioning
confidence: 98%
“…There are numerous examples in the literature of protozoa releasing large amounts of material into the extracellular space as a form of cellular communication with host cells (Garcia-Silva et al, 2014;Linhares-Lacerda et al, 2015;Fernandez-Calero et al, 2015;Cestari et al, 2012). In Giardia intestinalis, the diarrhoea and malabsorption could be a direct result of the interaction of the parasite with the intestinal epithelium which might be mediated by the parasite itself, or by substances it secretes or by MVs that could alter neighbouring cells.…”
Section: Exosome and Microvesicles Content Can Alter Neighbouring Cellsmentioning
confidence: 99%